– The Role of Social Media Networks to Support Public Relation Activities in Public Organizations –A Field Study - Tawakul, Shahd (Journal of Humanities & Social Sciences, 2018)
The study sought to identify the role of social media in supporting public relations activities in the Saudi public organizations, In order to achieve these objectives, the study based on the descriptive approach and the survey questionnaire used to collect data. The study applied in the Mecca city on a sample of public relations departments in public organizations (12) organizations with (85) public relations employees were selected in a simple random way. The study reached a number of results the most important of it were: The most prominent social media used were: (Twitter - Facebook - YouTube) - One of the most important using social media were Media coverage of organized events - Participation in public cultural and social activities such as: National Day - International Day (Women - Health - Traffic...) - Public outreach and use of the services of the Organization- The majority of employees in the public relations department of public organizations were males.
Keywords: social networks; public relations activities; public organizations